Character animation using reinforcement learning and imitation learning algorithms - Tahmid, Tokey; Lobabah, Mohammad Abu; Ahsan, Muntasir; Zarin, Raisa; Anis, Sabah Shahnoor (2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.